(untitled) (The Strategic Review for Southern Africa, 2020)
Decolonisation has been said to be “working toward a vision of human life that is not structured by the forced imposition of one ideal of society over those that differ”. This paper argues that political independence, responsive to the “dialectics of identity, liberation, recognition and distribution”, is not a sufficient condition for decoloniality of being as well as decoloniality of power and knowledge; and that political independence addresses coloniality of being without confronting coloniality of power and knowledge. Scholars committed to substantive decolonisation are bound to decolonise knowledge. Decolonisation of knowledge presents at least the conceptual possibility of a decoloniality of power. Decoloniality of knowledge itself, and thus the true liberation of the academy, becomes a realistic operational possibility, though requiring considerable application. This effort is vitally important given the deep alienation of South African university students. The trend to mimic exogenous experts and sages accentuates this imperative. Apart from the trend being futile, wasteful and dreary, it forecloses fresh insight and impedes the search for truth. The aim of this paper is to fill a gap in the sparse South African legal scholarship on decolonisation, principally the lack of definitional clarity